2004
DOI: 10.1007/s00181-003-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and economic growth in Australia: An empirical analysis

Abstract: The paper empirically examines the dynamic relationship between financial development and economic growth in Australia in terms of bank-based and market-based financial structure. A time-series approach using the VAR Model is used to provide evidence for the dynamic relationship. The paper provides empirical evidence on the causal impact of the financial market on the economic growth of the Australian economy. The results suggest that financial intermediaries and financial markets have different impacts on eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 19 publications
6
44
1
3
Order By: Relevance
“…Thus, we surmise that stock price and economic growth in Australia are comove in the long run over the analysis period of 1960 to 2007. This result is parallel with the finding of Mao and Wu (2007), but it is contrary with Thangavelu and Ang (2004) study. Since the variables are cointegrated, we estimate the long-run coefficients with four different long-run estimators to check for robustness of the estimation and also to provide more efficient long-run results.…”
Section: Source: Author's Calculationcontrasting
confidence: 54%
See 1 more Smart Citation
“…Thus, we surmise that stock price and economic growth in Australia are comove in the long run over the analysis period of 1960 to 2007. This result is parallel with the finding of Mao and Wu (2007), but it is contrary with Thangavelu and Ang (2004) study. Since the variables are cointegrated, we estimate the long-run coefficients with four different long-run estimators to check for robustness of the estimation and also to provide more efficient long-run results.…”
Section: Source: Author's Calculationcontrasting
confidence: 54%
“…403 401 As a value added to the earlier studies, Thangavelu and Ang (2004) applied both Johansen and Juselius (1990) multivariate cointegration and Granger causality tests to re-examine the linkages between stock price and economic growth in Australia over the period of 1969:Q1 to 1999:Q4. Their empirical evidence suggested that stock price and economic growth in Australia are not cointegrated.…”
Section: The Linkage Between Stock Price and Economic Growth Inmentioning
confidence: 99%
“…See, e.g.,King and Levine (1993a),Levine and Zervos (1998),Rajan and Zingales (1998),Beck et al (2000),Levine et al (2000), Levine (2002, 2004),Rioja andValev (2004), andMcCaig andStengos (2005), among others.3 See, e.g.,Demetriades and Luintel (1996),Luintel and Khan (1999),Rousseau (1999),Xu (2000),Bell and Rousseau (2001),Rousseau (2003), andThangavelu and Ang (2004), among others. 4 AsDemetriades and Andrianova (2004) explain, the existence of a sound financial system is a precondition for the economy to materialize new innovations and exploit its resources efficiently.…”
mentioning
confidence: 98%
“…SeeThangavelu and Ang (2004) for an empirical analysis that uses both bank-based and market-based financial indicators to assess the finance-growth link for Australia. 10 Principal component analysis has traditionally been used to reduce a large set of correlated variables into a smaller set of uncorrelated variables, known as principal components (seeStock and Watson, 2002a,b).…”
mentioning
confidence: 99%
“…Number 1 Spring 2013 Thangavelu et al (2004) Australia Sample VAR Methodology They found causality from economic growth to the development of financial intermediaries, although they could not find evidence that the development of financial markets would cause economic growth. Christopoulos and Tsionas (2004) 10 Developing Countries Panel Co-integration Analysis They found evidence that economic growth was the cause of financial development.…”
Section: Volumementioning
confidence: 99%